1994
DOI: 10.3801/iafss.fss.4-1125
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison Between Five Structural Fire Codes Applied To Steel Elements

Abstract: A comparison program has been established concerning the simulation of the static behaviour of steel columns submitted to fire [I]. The stress strain relationships in steel are those recommended in EC3, part 10 121. The five numerical codes used in this comparison are briefly described, namely CEFICOSS, DIANA, LENAS, SAFIR and SISMEF. A description of 8 tests is given: Lee's frame at ambient and at elevated temperatures, an eccentrically loaded column at ambient temperature, at uniform elevated temperature and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The tests have been simulated with the code SAFIR [3] and with the code Fires -Frame I [4,5]. The calculated temperatures are in good agreement with the experimental results, and were applied to the calculations of structural fire behaviour.…”
Section: The Simulationsmentioning
confidence: 74%
See 1 more Smart Citation
“…The tests have been simulated with the code SAFIR [3] and with the code Fires -Frame I [4,5]. The calculated temperatures are in good agreement with the experimental results, and were applied to the calculations of structural fire behaviour.…”
Section: The Simulationsmentioning
confidence: 74%
“…Franssen and Schneider have recently updated the model proposed in [I], and Franssen has introduced it in the code SAFIR which is being developed at the university of Liege [3]. While spending a year in Vienna, Morita has also incorporated this updated version of the Schneider model in the code Fires -Frame I developed at Chiba University [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Finite element models of the structural components were developed using the ANSYS parametric design language (Franssen, 1995) and coupled with fire simulations to predict their thermal response. Figure 2-2 is a finite element representation of the 3.05 m long steel bar.…”
Section: Model Simulationsmentioning
confidence: 99%
“…It has initially been published by Franssen et al [25] and has shown that five different computer codes using beam finite elements and under increasing temperature give similar results. The structure is shown in Figure 13.…”
Section: Lee's Frame At Elevated Temperaturesmentioning
confidence: 50%
“…The results under fire conditions have been compared with the same finite element software as have been used for the comparison at room temperature [25]. It can be seen ( Figure 14) that in case of bending (SAFIR-Bending) the shell element of SAFIR gives results close to the beam element.…”
Section: Figure 14 Horizontal Displacement Vs Temperaturementioning
confidence: 97%